The secrets of ancient ritual sites : the citadel of Machu Picchu and Stonehenge - Regas, Ricard; Cañagueral, Albert (Secrets of history., 2018)
Examines the ancient sites of Machu Picchu and Stonehenge. Highlights facts about their construction, how the structures were likely used, and what life was like for those living and worshipping there. Presents artifacts found at the sacred locations. Includes a glossary, resources for further information, and color photographs.